Modelling the short-T2* signal in the liver with ultrashort echo time magnetic resonance imaging (UTE-MRI) - Siu, AG (2019)
Liver fibrosis, a consequence of most chronic liver diseases, is characterised by collagen deposition. Collagen has a short-T2* signal that is undetectable with conventional magnetic resonance (MR) sequences. However, collagen signal is measurable with the ultrashort echo time (UTE) sequence, which can achieve an echo time of less than 1 ms. This thesis explored the modelling of the short-T2* signal in the liver with UTE.